The Social Impact of Citraraya Housing Development on the Community of Pematang Gajah Village - Nazwa Aulya Sriyadi; Asep Hariyanto (Jurnal Riset Perencanaan Wilayah dan Kota, 2026)
Abstract. Large-scale housing development in peri-urban areas often triggers complex socio-economic transformations in surrounding rural communities. This study aims to comprehensively analyze the social impacts of the Citraraya housing development on the local community of Pematang Gajah Village, Muaro Jambi Regency. Utilizing a concurrent mixed-method approach, primary data were collected through structured questionnaires (124 respondents purposively sampled based on an impact gradient), in-depth interviews with key community figures, and systematic field observations. Quantitative findings reveal a high aggregate social impact (Social Impact Index = 0.78). Security (mean 4.29) and solidarity (mean 4.14) were perceived most strongly, indicating enhanced collective well-being and social cohesion. However, lifestyle changes were more moderate (mean 3.20), and social interactions between original residents and newcomers, while harmonious, were not yet fully intensive (mean 3.65). Qualitative analysis triangulates these results, highlighting the role of collaborative activities (e.g., community sports, religious events) facilitated by the development in strengthening bridging social capital, despite emerging social segmentation. The study concludes that while the housing project has bolstered perceived security and solidarity through new platforms for interaction, it has not radically altered core lifestyles or achieved deep social integration. Challenges of segmentation persist. Therefore, the research recommends that developers and local policymakers implement more proactive and inclusive community-building programs, foster regular collaborative activities, and adopt a socially sensitive planning approach to ensure sustainable and integrative social outcomes in peri-urban transformations. These findings contribute to the literature on the social dynamics of planned urbanization in the Indonesian context.